2015
DOI: 10.1016/j.bbagrm.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated regulation of Nrf2 and histone H3 serine 10 phosphorylation in arsenite-activated transcription of the human heme oxygenase-1 gene

Abstract: Expression of the antioxidant gene heme oxygenase-1 (HO-1) is primarily induced through NFE2-related factor 2 (Nrf2)-mediated activation of the antioxidant response element (ARE). Gene transcription is coordinately regulated by transcription factor activity at enhancer elements and epigenetic alterations such as the posttranslational modification of histone proteins. However, the role of histone modifications in the Nrf2-ARE axis remains largely uncharacterized. The environmental contaminant arsenite is a pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 75 publications
3
20
0
Order By: Relevance
“…Studies have suggested that arsenicinduced H3 phosphorylation might be responsible for the up-regulation of the oncogenes c-fos and c-jun (65). Most recently, Ray et al reported that iAs induces a coordinated regulation of Nrf2 and histone H3S10 phosphorylation, which activates the human heme oxygenase-1 gene (HMOX1) (52). These results reinforce the notion that iAs modulates gene expression by operating through the JNK and p38/Mpk2 kinase pathway to promote cancer.…”
Section: Histone Modificationssupporting
confidence: 76%
See 1 more Smart Citation
“…Studies have suggested that arsenicinduced H3 phosphorylation might be responsible for the up-regulation of the oncogenes c-fos and c-jun (65). Most recently, Ray et al reported that iAs induces a coordinated regulation of Nrf2 and histone H3S10 phosphorylation, which activates the human heme oxygenase-1 gene (HMOX1) (52). These results reinforce the notion that iAs modulates gene expression by operating through the JNK and p38/Mpk2 kinase pathway to promote cancer.…”
Section: Histone Modificationssupporting
confidence: 76%
“…These changes include increases in H3K9me2, H3K4me3, and H3S10, decreases in H2B ubiquitination, and either increases or decreases in H3K27me3 (47)(48)(49)(50)(51)(52). In addition, following iAs exposure in humans, blood cells exhibited an overall decrease in H3K9me3 and H3K9ac, with an increase in H3K9me2 (47,48).…”
Section: Histone Modificationsmentioning
confidence: 97%
“…residues of Keap1 protein, resulting in the disruption of the contact between Keap1 and Nrf2 [11,[14][15][16]. Meanwhile, burgeoning evidence suggests that Nrf2 also targets mircroRNAs (miRNAs) that are involved in cell metabolism, adhesion, tumorigenesis and so on [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that iAs exposure induces global and gene-specific post-translational histone modifications such as reduction of acetylation in histone H3 and H4: loss of H4Lys 16 10 and H2AX phosphorylation, and decreases in H2B ubiquitination (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%